PATEN TERHADAP APLIKASI PROGRAM KOMPUTER BERBASIS FINANCIAL AND TECHNOLOGY DI INDONESIA - Anik Marfistasari; Ennys Kurniawati; Badzlina Putri Indraswati (Fakultas Hukum Universitas Narotama, 2019)
Patents as Intellectual Property Rights which are included in exclusive rights that contain legal construction. It basically must provide legal protection for the application of financial and techology-based on computer programs in Indonesia, where it is given to the novelty of the invention, inventive steps contained in it; and the success of inventions that should be applicable in industries that are developing at this time. To get tsshe assurance and legal protection against fintech programs invention, it is necessary to be followed up on legislation in the field of intellectual property, especially in terms of special patents which it related the fintceh programs inventions in Indonesia, which are expected to provide solutions to the legal problems in Indonesia and to provide a clear legal direction related the fintech programs inventions, on the other hand, with the existence of the legislation in the field of special patent it is expected that can obtain balanced legal protection related to computer programs. Which must be in accordance with the purpose of the invention itself to support the maximum efforts to achieve people's welfare .